Effect of Chloroquine on Glucose Metabolism - Gaafar, Khadiga M.; Khedr, Mona I.; Bashandy, Samir A.; Sharaf, Olaa A.; El-Zayat, Salwa R. (Arzneimittelforschung, 2002)
The long- and short-term effects of chloroquine (CAS 54-05-7) on glucose metabolism in rats were assessed. The long-term chronic chloroquine administration (5 and 10 mg/kg b.w. 6 days a week for 6 months) caused a decrease in serum glucose, insulin, calcium, potassium and protein levels, while the glucagon level increased. The short-term acute effect of chloroquine administration (10 mg/kg b.w. 6 days for one week) caused an improvement in glucose tolerance as shown by the decrease in glucose and insulin curves after an oral glucose tolerance test. This was accompanied by an increase in insulin activity, corrected insulin response, and glucose tolerance parameter and a decrease in glucose and insulin areas. Lactate dehydrogenase and glucose-6-phosphate dehydrogenase activities were increased, too, indicating an increase which provides the needed energy for overcoming the injurious effect of chloroquine.
Keywords: CAS 54-05-7; Chloroquine, effect on glucose metabolism, rat